2017
DOI: 10.1021/acs.jpcc.7b08923
|View full text |Cite
|
Sign up to set email alerts
|

Breaking Down a Complex System: Interpreting PES Peak Positions for Cycled Li-Ion Battery Electrodes

Abstract: Photoelectron spectroscopy (PES) is an important technique for tracing and understanding the side reactions responsible for decreasing performance of Li-ion batteries. Interpretation of different spectral components is dependent on correct binding energy referencing, and for battery electrodes, this is highly complex. In this work, we investigate the effect on binding energy reference points in PES in correlation to solid electrolyte interphase (SEI) formation, changing electrode potentials, and state of charg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(58 citation statements)
references
References 37 publications
(62 reference statements)
3
54
0
Order By: Relevance
“…The latter is very important, as this is, to the best of our knowledge, the first HAXPES evidence for the lithium-trapping effect. By comparing the positions of the peaks in Figure 4 with those reported in our previous work involving step-by-step lithiation of silicon, [23] it can be seen that the spectra for the 25th cycle match those previously obtained using a lithiation capacity of Adv. Energy Mater.…”
Section: Hard X-ray Photoelectron Spectroscopy (Haxpes) Analyses Of Ssupporting
confidence: 75%
See 2 more Smart Citations
“…The latter is very important, as this is, to the best of our knowledge, the first HAXPES evidence for the lithium-trapping effect. By comparing the positions of the peaks in Figure 4 with those reported in our previous work involving step-by-step lithiation of silicon, [23] it can be seen that the spectra for the 25th cycle match those previously obtained using a lithiation capacity of Adv. Energy Mater.…”
Section: Hard X-ray Photoelectron Spectroscopy (Haxpes) Analyses Of Ssupporting
confidence: 75%
“…After the first lithiation, a new peak due to the Li–Si alloy emerged at lower binding energies (see the yellow Li z Si peak in Figure ) in addition to the silicon peak. In the spectra for the cycled electrode, the silicon peak was denoted Li x Si to indicate that the electrode also contained some residual lithium yielding a shift toward lower binding energies . The latter shift should, incidentally, be coupled to the shift in the redox potential of the electrode to lower potentials expected for an increasing lithium concentration in the electrode (see Section ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…18,25 At the lower binding energy side, a new doublet at about 160.6 eV (2p 3/2 ) was observed when using Super C65, CNF or no additive in the cathode composite, stemming from the formation of Li 2 S. 29,30 Interestingly, the peaks related to PS 4 3À were shied by 0.4-0.5 eV to higher binding energies relative to the pristine state when Li 2 S was apparent. This may be due to charging or electronic interface effects during the measurement because of the insulating nature of Li 2 S. 31,32 Nevertheless, the distinct mechanisms leading to Li 2 S and SO x formation are yet to be resolved. We also note that the Ti 2p peaks showed some shi in binding energy aer cycling ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Also, as shown in a recent study, a buried interphase potential difference that increases with cycling has been observed that can cause quite large shifts-on the order of nearly 2 eV-in the C 1s peak associated with the SEI. 17 Furthermore, hydrocarbon species in the electrode at different stages of cycling (for example, those in a pristine electrode vs. those in an SEI) might not be the same, and therefore could have differing BEs.…”
Section: Introductionmentioning
confidence: 99%